2007
DOI: 10.1128/aem.01002-07
|View full text |Cite|
|
Sign up to set email alerts
|

Microbial Composition and Structure of Aerobic Granular Sewage Biofilms

Abstract: Aerobic activated sludge granules are dense, spherical biofilms which can strongly improve purification efficiency and sludge settling in wastewater treatment processes. In this study, the structure and development of different granule types were analyzed. Biofilm samples originated from lab-scale sequencing batch reactors which were operated with malthouse, brewery, and artificial wastewater. Scanning electron microscopy, light microscopy, and confocal laser scanning microscopy together with fluorescence in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(102 citation statements)
references
References 41 publications
3
96
1
2
Order By: Relevance
“…For example, the observations of Weber et al [46], suggesting that protozoa and fungi were crucial initially in providing the matrix for bacterial growth and EPS production in their granules, are quite diVerent from the situation with those examined here. Consequently, it may not be possible to sustain a uniWed mechanistic theory for granulation, although its common feature is that it seems to occur mainly in SBR systems [34].…”
Section: Discussioncontrasting
confidence: 80%
“…For example, the observations of Weber et al [46], suggesting that protozoa and fungi were crucial initially in providing the matrix for bacterial growth and EPS production in their granules, are quite diVerent from the situation with those examined here. Consequently, it may not be possible to sustain a uniWed mechanistic theory for granulation, although its common feature is that it seems to occur mainly in SBR systems [34].…”
Section: Discussioncontrasting
confidence: 80%
“…These bacteria are capable to store sulphur granules and PHA; and have rapid nutrients uptake rates under nutrient deficiency. The outgrowth of these bacteria in aerobic granules cultivated with brewery wastewater has been previously reported [38] and they were thought to be responsible of the bulking and settling problems, probably caused by the high applied OLR (3.6 kg COD s /(m 3 d)), the dissolved oxygen deficiency or the high temperatures of operation reported in that research. In the present research the presence of Thiothrix was observed in the reactor treating fish canning effluent with large salts content.…”
Section: Effects Of Operational Conditionsmentioning
confidence: 61%
“…Recent studies indicate that fungal hyphae also act like skeletal elements in the structural formation process [29,38]. Weber et al [38] observed that filamentous fungal pellets dominated the sludge population in the first 10 to 15 days and they served to initiate the granular biofilm structure as an immobilizing matrix for bacteria. These authors checked that these fungi were still present in mature granules, where they supported the development and maintenance of the granular structure.…”
Section: Effects Of Operational Conditionsmentioning
confidence: 99%
“…Granules creating aerobic granular activated sludge are considered as aggregates of microorganisms, mainly bacteria, and extracellular polymeric substances [4]. Aerobic granular sludge also functions as a biofilm in suspension, which is composed of combining cells [5]. The application of granules for wastewater treatment has many advantages.…”
Section: Introductionmentioning
confidence: 99%
“…They settle significantly faster than activated sludge flocs (high settling velocity). In addition, granular sludge provides high and stable rates of metabolism [5].…”
Section: Introductionmentioning
confidence: 99%